Pedestrian and transit accessibility on a micro level: Results and challenges - van Eggermond, Michael A.B.; Erath, Alex (Journal of Transport and Land Use, 2015)
In this paper, we connect two notions of accessibility that are more often than not considered separately: pedestrian accessibility and transit accessibility. We move away from the notion of zonal accessibility and measure fine-grained accessibility using door-to-door travel times. Two pedestrian networks are compared to a baseline scenario considering Euclidean distances for a large metropolitan area in which each individual building is considered as an activity opportunity. It is shown that pedestrian accessibility to jobs differs when pedestrian distances are approximated with different networks that are more representative of reality. Stop-to-stop public transport travel times are extracted from an agent-based simulation of public transport smart card data. The effect of less-than-optimal connections from transit to the pedestrian network, a local measurement, can be seen when calculating the accessibility to all destinations in the city. We suggest moving away from Euclidean-based distance analyses. Limitations can be found in the data available; the connection of buildings to the network becomes important, as does the inclusion of pedestrian crossings. For an inclusive accessibility measure, it will be necessary to calculate generalized costs for pedestrians and generate different pedestrian networks that reflect the limitations of different user groups.